Purification of a new isoform of laccase from a Marasmius quercophilus strain isolated from a cork oak litter (Quercus suber L.) - Farnet, A. M.; Criquet, S.; Pocachard, E.; Gil, G.; Ferré, E. (MYCOLOGIA, 2002)
A new isoform of laccase from Marasmius quercophilus is described in this study. The strain of this white-rot fungus was isolated for the first time on a cork oak litter. This isoform exhibited certain common properties of laccases (a molecular weight of 65 Kda, an optimum pH of 6.2 with syringaldazine). But this laccase has also particularly novel features: the best activity measured was observed at high temperatures (80 C) and this isoform was not inhibited with EDTA. Furthermore, this induced laccase was able to transform most of the aromatic compounds tested without the addition of mediators to the reaction mixture, and the transformation of certain chlorophenols (2-chlorophenol and 2,4-dichlorophenol) by a laccase isoform from M. quercophilus is reported here for the first time. We also demonstrate the importance of 2,2'-azinobis(3-ethylbenzthiazoline-6-sulfonate) (ABTS) as a mediator since it allowed veratryl alcohol and p-hydroxybenzoic acid transformation. Moreover, new products of transformation were observed using the combination of ABTS with this isoform of laccase.
The following values have no corresponding Zotero field: pub-location: PUBLICATIONS DEPT, BRONX, NY 10458 USA publisher: NEW YORK BOTANICAL GARDEN
Keywords: aromatic compounds; mediator; polyphenoloxidase; white-rot fungus